(untitled) (Eurasian Medical Research Periodical, 2023)
Recently, there has been a great scientific and practical interest in psychosomatic relationships in cardiology, in connection with the unfavorable dynamics of two clinical forms predicted by WHO experts for the coming decades - coronary heart disease and depression with a reduction in the duration of a working, socially fulfilling life.